GINGIVAL STATUS AND ORAL HYGIENE HABITS IN CHILDREN BETWEEN 10-12 YEARS - Zornitsa Lazarova; Hristina Tankova; Liliya Doichinova (Peytchinski Publishing, 2024)
Introduction: Children's adolescence is characterized by dynamically changing indicators of periodontal and oral health, related mainly to the eruption of the permanent dentition and stabilization of the periodontal space. This age period is also characterized by an increased incidence of gingival diseases, with the dental biofilm being the main risk factor for the inflammatory process. Aim: The aim of this study is to assess the relationship between gingival status, oral hygiene habits and knowledge on topics related to oral health in children aged 11-13. Material and methods: The subject of the study was 106 children aged 11-13 years. All children overwent a clinical periodontal examination and periodontal risk assessment at 4 levels. An electronic periodontal probe PA ON (Orangedental) with specially designed software was used to assess periodontal and oral hygiene status. The study included a survey method for assessing children's knowledge on topics related to oral health with periodontal focus. The survey consists of 38 questions divided into eight topics. Results: All the children aged 11-13 years had an initial form of gingival inflammation, against the background of plaque accumulation affecting more than 69% of tooth surfaces, unstable and irregular oral hygiene habits, as well as insufficient knowledge of oral/periodontal health. Through appropriate preventive programs, this age is best suited to create consciously motivated behavior for proper oral hygiene and oral health.